2022
DOI: 10.3390/nano12101712
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Electronic, Magnetic and Optical Properties of Non-Metal Atoms Adsorbed onto Germanium Carbide

Abstract: Nine kinds of non-metal atoms adsorbed into germanium carbide (NM-GeC) systems wereare investigated by first-principles calculations. The results show that the most stable adsorption positions vary with the NM atoms, and C-GeC exhibits the strongest adsorption. The adsorption of NM atoms causes changes in the electronic, optical and magnetic properties of the GeC system. F- and Cl-GeC turn into magnetic metals, P-GeC becomes a half-metal and H- and B-GeC appear as non-magnetic metals. Although C- and O-GeC rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The DFT-3 method describes weak dispersion forces between layers [29,30]. The truncation energy of the plane wave is set to 500 eV [31]. The Brillouin zone is described by 3 × 3 × 1 K-points centered on Γ point.…”
Section: Computation Methods and Modelsmentioning
confidence: 99%
“…The DFT-3 method describes weak dispersion forces between layers [29,30]. The truncation energy of the plane wave is set to 500 eV [31]. The Brillouin zone is described by 3 × 3 × 1 K-points centered on Γ point.…”
Section: Computation Methods and Modelsmentioning
confidence: 99%
“…This carbide is a semiconductor with a wide bandgap, that has been employed for technological applications as biosensors, photocatalytic processes, field emission transistors, nanoelectronics, membrane technology, photothermal or photodynamic activities, medical implants, etc [6]. On the other hand, theoretical studies about germanium carbide (GeC) and tin carbide (SnC) suggest that their nanostructures could be materials for protective coatings [7], microelectronics [8][9][10] and energy [11][12][13] applications and spintronic devices [14,15]. Then, the PbC is a promising material for technological applications since its properties could be similar to those of SiC, GeC and SnC.…”
Section: Introductionmentioning
confidence: 99%
“… Zhang et al (2014) report that B, N, or C doped g-ZnO exhibits strong chemisorption for CO. Wang et al ( Cui et al, 2019 ) conducted a mixed density functional study on the effects of rotation angle and biaxial strain on g-ZnO/TMDCs heterojunctions. In addition to doping and building heterojunctions, adsorption ( Zhang and Cui, 2022b ) is another efficient way to modify 2D materials. Cui et al ( Wang et al, 2018b ; Cui et al, 2020d ; Cui et al, 2021c ) demonstrated the possibility of reducing the work function of g-GaN adsorption and increasing the absorption of visible light via absorbing transition metals (TMs).…”
Section: Introductionmentioning
confidence: 99%